THE CORRELATION BETWEEN STUDENTS’ SPEAKING ABILITY AND THE MASTERY OF GRAMMAR AT THE ELEVENTH GRADE - silfani fani (UKI TORAJA, 2017)
The objective of the research to find out whether or not there is a significantcorrelation between Students’ Speaking Ability and the Mastery of Grammar at theEleventh Grade Students of SMA Kristen Barana’.In this research, the writer usedcorrelational method in a quantitative design.Thepopulation of this research is the eleventh grade students of SMA Kristen Barana’academic year 2017/2018. It consists of five classes. The number of populationare125 students. The writer took 20 students as sample they were chosen using byrandom sampling technique which took 10 students from Exact class and 10students from Social class. The instrument used to take the data was written testand oral test. It was used to find out the students’ ability in speaking and to find outthe students mastery in grammar.The result of data analysis showed there is positive correlation between students’speaking ability and mastery of grammar at the eleventh grade students of SMAKristen Barana’. This was proved by the result of coefficient correlation is 0,870.The result of data analysis also showed there is significant correlation betweenstudents’ speaking ability and their mastery in grammar of the eleventh gradestudents of SMA Kristen Barana’. This was proved by the result of significantcorrelation is7, 486.Based on the result above, it can be concluded thatthere is positive and significantcorrelationbetween students’ speaking ability and